Academic Status for College and University Librarians in Karnataka: A Study - Kannappanavar, B. U. (Journal of Information and Knowledge, 2002)
Librarians are generalist teachers. They strive hard to enhance the academic standards of both the teachers and the students by providing timely information in right proportions at various levels. But still their services are not considered on par with the regular teachers. An attempt has been made here to trace the library of struggle of the librarians to gain academic status on par with of teachers in colleges and universities. The suggestions and accommodations of various committees and commissions have not helped the community much. Even the government’s orders have not been implemented is may cases the struggle goes on.